A criptografia motivando o estudo das funções no 9º ano do ensino fundamental - Moura, Moisés de Oliveira (Universidade Federal do Tocantins, 2019)
The cryptography arises in the technological and communication media as part of the reality of our students, however, some of the students still do not know this. In this way, establishing a connection between the cryptography contained in this context and the content seen in the classroom can generate positive results in the school environment. With this in mind, the purpose of this work is to present the cryptography as a tool to contextualize the content of functions, in particular, the affine functions. With the intention of enriching the teaching of Mathematics and awakening in the student the interest in Mathematics, the cryptography was added to the content of the functions affine to the 9th year of Elementary School. Relating the teaching of functions to cryptography is a way of informing him that everything he has studied up to then, however basic, is applicable and useful, in this essential case, to the safe development of technology. For the development of the work, a strategy was established with the students, started with a pre-test with the objective of verifying their knowledge in relation to the topic addressed; Then, historical aspects of cryptography and functions were raised, and finally, the connection between the two themes was made, totaling 6 (six) encounters. Data were collected through pre-test, post-test and responses to activities. In addition, a bibliographic study was carried out, which gives the research a qualitative character and aims to facilitate the understanding of the content of the affine functions, through the contextualization provided by the relation established between the cryptography and the functions.